Estado nutricional de menores de 5 anos de idade no Brasil: evidências da polarização epidemiológica nutricional - Lyra, Clélia de Oliveira (2017)
The objective of this study was to evaluate the nutritional status of children under 5 years of age in Brazil in 2009 and its association with social and demographic factors. Data from the Household Budget Survey (Pesquisa de Orçamento Familiar - POF 2008-2009) were used, in which the nutritional profile was evaluated according to the weight-for-age (W/A), height-forage (H/A) and weight-for-height (W/H) indices (n = 14,569). The association was estimated by applying the Pearson association test, a logistic regression and a correspondence analysis. The correspondence analysis showed a higher association of thinness with children in the North and Northeast regions, in families with lower levels of income and in those of black colour/race. Overweight and obesity had a stronger relationship with children living in the South, Southeast and Central-West, in males, in those from urban areas, in those of Caucasian colour/race, in those aged 3 years and in those from families with intermediate income ranges. Overweight and obesity showed a heterogeneous spatial distribution amongst Brazilian states. A nutritional epidemiological polarisation that presents a major challenge for public health is indicated: we must reduce nutritional deficiencies and promote healthy eating habits from childhood to improve the nutritional and epidemiological profiles and mortality of the population